Patients' Autonomy at the End of Life: A Critical Review - Houska, Adam; Loučka, Martin (Journal of pain and symptom management, 2019)
CONTEXT: The predominating definition of autonomy as a capacity to make an independent rational choice may not be suitable for patients in palliative care. Therefrom arises the actual need for more contextualized perspectives on autonomy to promote the quality of life and satisfaction with care of terminally ill patients. OBJECTIVES: This review aimed to develop a theoretical structural model of autonomy at the end of life based on patients' end-of-life care preferences. METHODS: In this review, we used systematic strategy to integrate and synthesize findings from both qualitative and quantitative studies investigating patients' view on what is important at the end of life and which factors are related to autonomy. A systematic search of EMBASE (OVID), MEDLINE (OVID), Academic Search Complete (EBSCO), CINAHL (EBSCO), and PsycINFO (EBSCO) was conducted for studies published between 1990 and December 2015 providing primary data from patients with advanced disease. RESULTS: Of the 5540 articles surveyed, 19 qualitative and eight quantitative studies met the inclusion criteria. We identified two core structural domains of autonomy: 1) being normal and 2) taking charge. By analyzing these domains, we described eight and 13 elements, respectively, which map the conceptual structure of autonomy within this population of patients. CONCLUSION: The review shows that maintaining autonomy at the end of life is not only a concern of making choices and decisions about treatment and care but that emphasis should be also put on supporting the patients' engagement in daily activities, in contributing to others, and in active preparation for dying.
Keywords: kvalita života; Humans; Personal Autonomy; quality of life; terminally ill; pacientova volba; Terminal Care; end of life; osobní autonomie; Quality of Life; Patient Preference; patient preference; péče o umírající; palliative care; Autonomy; Palliative Care; lidé; paliativní péče